Phase field crystal simulation of the structure evolution between the hexagonal and square phases at elevated pressures - Shuai X.; Mao H.; Kong Y.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Based on the two-mode phase field crystal (PFC) model and the principle of the common tangent, a two-dimensional PFC phase diagram is established. According to the phase diagram, the parameters for a steady growth of the hexagonal and the square phase are found. Moreover, the nucleation and growth characteristics of the square phase from hexagonal phase under different pressures are simulated by using these parameters. The movements of dislocation core under pressure at different transformation stages are revealed and compared with each other. Finally, by changing the grain orientation, the formation and disappearance of grain boundaries at different angles are simulated and analyzed.